Postpartum Depression in Primigravida: The Influence of Maternal Factors in Indonesia - Siti, Putri Rafika; Yuniastuti, Ari; Cahyati, Widya Hary (Journal of Creativity Student, 2025)
Background: Postpartum depression (PPD) is a common non-psychotic mental disorder that occurs after childbirth and negatively impacts maternal quality of life, child development, and family stability. This study aims to analyze the association between maternal factors and the incidence of PPD in primigravida mothers in Indonesia based on the 2023 Indonesian Health Survey (SKI) data. Methods: This study used a cross-sectional design with the source of data from SKI 2023. The study subjects were 36956 primigravida mothers with infants ≤6 months of age. Postpartum depression was measured using the Indonesian version of the Mini International Neuropsychiatric Interview (MINI). Bivariate and multivariate logistic regression were used to identify factors associated with the incidence of PPD. Results: The prevalence of PPD in primigravida mothers was 6.4%. Factors that were significantly associated with PPD included: region of residence (p = 0.001), abuser relationship (p = 0.001), marital status (p = 0.001), and no antenatal care check-up (p = 0.001). Maternal age, pregnancy complications, and delivery complications showed no statistically significant association with PPD (p > 0.05). Conclusion: These findings can help in the development of policies focusing on community-centered approach, as well as enhanced mental health services for mothers to assist in the prevention of PPD.